Kaidah Hukum Eksistensi Jaksa Pengacara Negara pada Badan Usaha Milik Negara - Ismanto, Ismanto (Banua Law Review, 2021)
Abstract: When referring to the law, there is no firmness, the prosecutor's obligation to represent the government is only related to the interests of the state or the government in its capacity as a public legal entity. In this position the government represents the State which is facing legal problems. although it is known that Presidential Regulation No. 38/2010 concerning the Organization and Work Procedure of the Indonesian Prosecutor's Office which states that the scope of the civil and state administration includes law enforcement, legal aid, legal considerations and other legal actions against the state or government, including state institutions / agencies, institutions / central and regional government agencies, State / Regional Owned Enterprises in the civil and state administration sector, should still pay attention to the measuring positions of the parties in a case so that things do not go wrong.keyword : Rule of Law, Lawyer, StateAbstrak : Apabila mengacu pada Undang-Undang tidak ditemukan adanya ketegasan, kewajiban Jaksa mewakili pemerintah hanya terkait dengan kepentingan negara atau pemerintah di dalam kapasitasnya sebagai Badan Hukum Publik. Di dalam kedudukan ini pemerintah merepresentasikan Negara yang sedang menghadapi permasalahan hukum. walaupun diketahui bahwa Peraturan Presiden Nomor 38/2010 tentang Organisasi dan Tata Kerja Kejaksaan RI yang menyatakan lingkup bidang perdata dan tata usaha negara meliputi penegakan hukum, bantuan hukum, pertimbangan hukum dan tindakan hukum lain kepada negara atau pemerintah, meliputi lembaga/badan negara, lembaga/instansi pemerintah pusat dan daerah, Badan Usaha Milik Negara/Daerah di bidang perdata dan tata usaha negara, seyogyanya tetap memperhatikan pada takaran kedudukan para pihak yang berperkara agar tidak terjadi hal yang tidak semestinya.Kata Kunci : Kaidah Hukum, Pengacara, Negara